Boys born with hypospadias and fetal growth restriction exhibit shorter anogenital distances: a retrospective cross-sectional study - Pan, Wenfeng; Wu, Min; Chen, Yan; Xie, Hua; Huang, Yichen; Chen, Fang (Frontiers in Pediatrics, 2025)
BackgroundHypospadias is a common congenital urological malformation in males, potentially associated with inadequate prenatal androgen exposure. Anogenital distances (AGDs) are biomarkers of prenatal androgen action, while fetal growth restriction (FGR) may impair gonadal development and hormone levels. This study aims to investigate the relationship between AGDs and different severities of hypospadias, with a specific focus on the impact of FGR.MethodsA retrospective observational study was conducted on male pediatric patients treated at Shanghai Children's Hospital between August 2019 and January 2023. Patients were divided into the control group and the hypospadias group, with the latter further classified into distal, middle, and proximal subgroups based on urethral meatus location. AGDs, including anoscrotal distance (ASD), AGD-1, and AGD-2, were measured under anesthesia. Linear regression analysis was performed to assess the associations between AGDs, hypospadias severity, and FGR indicators, including low birth weight (LBW) and small for gestational age (SGA).ResultsA total of 386 pediatric patients were included, with 205 in the control group and 181 in the hypospadias group. Patients with hypospadias exhibited significantly shorter AGDs compared to the control group (P < 0.05). Among hypospadias subtypes, AGDs showed a decreasing trend with increasing severity of hypospadias (e.g., ASD: 39.0 ± 12.8 mm in distal vs. 31.8 ± 8.6 mm in proximal cases, P < 0.05). Linear regression analysis revealed that proximal hypospadias and SGA were significantly associated with shorter AGDs across all measurements (e.g., proximal hypospadias reduced ASD by 6.52 mm, 95% CI: −9.97 to −3.06, P < 0.001; SGA reduced ASD by 4.48 mm, 95% CI: −8.00 to −0.97, P = 0.01). Prematurity showed no significant association with AGDs.ConclusionBoys with hypospadias and FGR exhibit significantly shorter AGDs, with more severe hypospadias and SGA showing the strongest associations. This study provides a foundation for future clinical assessments and research into prenatal factors influencing male genital development.